Pengelolaan Media Sosial Instagram Humas Dinas Pendidikan Provinsi Jawa Barat - Risma Khotimah Risma; Erik Setiawan (UNISBA Press, 2022)
Abstract. Globalization changes all forms of communication into online media, this is also felt by public relations practitioners. Where public relations practitioners must start using social media in their public relations activities. This study will discuss the management of Instagram social media from the Public Relations of the West Java Provincial Education Office. Descriptive study is used as a method in this research, interview technique is used as the main source in obtaining data which is then supported by other data such as data from observations and documentation.The Hadil obtained in this study is that the Public Relations of the West Java Provincial Education Office has carried out Instagram social media management activities as a communication medium through social media in accordance with the Luttrell concept which explains 4 points including Share, Optimize, Manage, and Engage. However, there are still some things that need to be optimized again, such as in quick response activities, the admin must be able to respond quickly to the audience so that there is no negative reaction from the public. Abstrak. Globalisasi mengubah segala bentuk komunikasi menjadi media online, hal ini juga dirasakan oleh para praktisi humas. Dimana praktisi humas harus mulai menggunakan media sosial dalam kegiatan kehumasannya. Penelitian ini akan membahas tentang pengelolaan media sosial Instagram dari Humas Dinas Pendidikan Provinsi Jawa Barat. Studi deskriptif digunakan sebagai metode dalam penelitian ini, teknik wawancara digunakan sebagai sumber utama dalam memperoleh data yang kemudian didukung oleh data lain seperti data hasil observasi dan dokumentasi. Hadil yang diperoleh dalam penelitian ini adalah Humas Dinas Pendidikan Provinsi Jawa Barat telah melakukan kegiatan pengelolaan media sosial Instagram sebagai media komunikasi melalui media sosial sesuai dengan konsep Luttrell yang menjelaskan 4 poin diantaranya Share, Optimize, Manage, dan Terlibat. Namun masih ada beberapa hal yang perlu dioptimalkan lagi, seperti dalam kegiatan quick response, admin harus bisa merespon dengan cepat kepada audiensnya agar tidak terjadi reaksi negatif dari masyarakat.